Hubungan etika profesi, keahlian, pengalaman, dan situasi audit dengan ketepatan pemberian opini dalam audit laporan keuangan melalui pertimbangan materialitas dan skeptisisme profesional auditor - Wahyudi, Dwi Putra; DP, Emrinaldi Nur; Saidi, Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is to examine the relation between ethics, expertise, experience, and audit situation with accuracy of the issuing of audit opinion through materiality judgment and auditor’s professional scepticism as a mediating effect. Survey method is applied to the respondents consisting of auditors in registered public accounting firm in the IAPI directory in Batam, Pekanbaru, and Palembang.Data analysis conducted by using Partial Least Square (PLS) method withSmartPLS 2.0 M3 from sample of 61 developed questionnaire responses that were distributed to 18 public accounting firms.The result of this research indicate that ethics, expertise, and experience have significant relation with accuracy of the issuing of audit opinion. While, ethics and auditor’s professional scepticism have significant mediating effect through materiality judgment, then ethicts and audit situation have significant mediating effect through auditor’s professional scepticism. The R-Square obtained indicate that 85,53% accuracy of the issuing of audit opinion can be described by all independent and mediating variables, while the remaining 14,47% is described by other variables were not examined in this research.Key words : ethics, expertise, experience, audit situation, auditor’s professional scepticism, materiality judgment, audit opinion